Insights into the history of a bacterial group II intron remnant from the genomes of the nitrogen-fixing symbionts Sinorhizobium meliloti and Sinorhizobium medicae - Toro, N (Nature Publishing Group, 2014)
Group II introns are self-splicing catalytic RNAs that act as mobile retroelements. In bacteria, they are thought to be tolerated to some extent because they self-splice and home preferentially to sites outside of functional genes, generally within intergenic regions or in other mobile genetic elements, by mechanisms including the divergence of DNA target specificity to prevent target site saturation. RmInt1 is a mobile group II intron that is widespread in natural populations of Sinorhizobium meliloti and was first described in the GR4 strain. Like other bacterial group II introns, RmInt1 tends to evolve toward an inactive form by fragmentation, with loss of the 3′ terminus. We identified genomic evidence of a fragmented intron closely related to RmInt1 buried in the genome of the extant S. meliloti/S. medicae species. By studying this intron, we obtained evidence for the occurrence of intron insertion before the divergence of ancient rhizobial species. This fragmented group II intron has thus existed for a long time and has provided sequence variation, on which selection can act, contributing to diverse genetic rearrangements, and to generate pan-genome divergence after strain differentiation. The data presented here suggest that fragmented group II introns within intergenic regions closed to functionally important neighboring genes may have been microevolutionary forces driving adaptive evolution of these rhizobial species.